2000
DOI: 10.1111/j.1471-0528.2000.tb11105.x
|View full text |Cite
|
Sign up to set email alerts
|

Which women should be tested for Chlamydia trachomatis?

Abstract: ObjectiveDesign Cross sectional study. SettingPopulation Two thousand thirty-five sexually active women attending various outpatient settings. Main outcome measures ResultsTo assess the prevalence of genitourinary Chlamydia trachomatis infection among women in different clinical settings, with a view to making decisions about who should be tested routinely.One regional hospital and family planning clinic serving an urban centre.Prevalence of positivity by clinical setting, stratified by age.Overall, prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Macmillian et al reported similar prevalence and decreasing trend with age, where infection levels only dramatically decreased in women aged 30 and above. 9 This suggests that the upper age limit for screening in this study, as proposed by the chief medical officer's expert advisory group on C trachomatis 1 and thus likely to be used in a national programme, needs to be reviewed. Bias due to the self selection of cases will influence the prevalence seen; however, uptake of testing was universally high among all age groups and healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
“…Macmillian et al reported similar prevalence and decreasing trend with age, where infection levels only dramatically decreased in women aged 30 and above. 9 This suggests that the upper age limit for screening in this study, as proposed by the chief medical officer's expert advisory group on C trachomatis 1 and thus likely to be used in a national programme, needs to be reviewed. Bias due to the self selection of cases will influence the prevalence seen; however, uptake of testing was universally high among all age groups and healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a prevalence of between 1% and 29% depending on the population studied, the selection criteria and diagnostic tests used, with the highest rates found in under 25-year-olds. [5][6][7][8][9][10][11][12] Studies in other countries have shown that screening and treatment for C. trachomatis significantly reduces the prevalence of the infection and PID in women. [13][14][15] In 1998 the Chief Medical Officer (CMO) published the report of the CMO's Expert Advisory Group on Chlamydia trachomatis 5 which was set up to consider the practical implications of screening.…”
Section: Introductionmentioning
confidence: 99%
“…Macmillan et al found similar chlamydia prevalence rates in women attending for miscarriage (4.0%) and for TOP (5.7%), while Shankar et al described much lower rates for women presenting to an early pregnancy unit (1.96%). 6,10 Obviously further research is needed to confirm prevalence numbers for this group in our population.…”
Section: Discussionmentioning
confidence: 92%